Audience Polemic Toward President Jokowi's Policies on Facebook - Wahid, Umaimah; Saeno, Saeno; Martianto, Raden Wahyu Utomo (Jurnal Studi Jurnalistik, 2024)
Jokowi's and the government's policies addressing the COVID-19 pandemic have generated positive and negative reactions among social media users. The government/President Jokowi's policies are considered slow, indecisive, disorienting, changing, and confusing to the public. This study aims to uncover and interpret the significance of social media users' acceptance of President Jokowi's policies in addressing COVID-19. The research uses cultural studies, reception analysis, and text analysis theories. The study's findings reveal that individuals from diverse backgrounds, such as lecturers and researchers, despite having the same profession, interpret President Jokowi's leadership status differently on social media. The community perceives several presidential/government policies as irrelevant and lacking strategic value. The community expects strong leadership in handling a crisis as big as COVID-19. Some informants like and believe in President Jokowi's leadership style, while others believe in the government/president but hope for more strategic public policies. However, some informants who do not hold this belief view the policy as inappropriate, not strategic, and merely an image. In order to confront the COVID-19 pandemic as a national disaster, all country components must build collaboration and solidarity through appropriate policies.